Forebrain neuropeptide regulation of pair association and behavior in cooperating cleaner fish - Cardoso, Sónia C. (2015)
Animals establish privileged relationships with specific partners, which are treated differently from other conspecifics, and contribute to behavioral variation. However, there is limited information on the underlying physiological mechanisms involved in the establishment of these privileged ties and their relationship to individual cooperation levels. The Indo-Pacific bluestreak cleaner wrasse Labroides dimidiatus often forages in mixed-sex pairs when cleaning fish clients. Intra-couple conflicts often arise during a joint client inspection, which may alter the overall quality of cleaning service provided. Here we tested two hypotheses: a) whether intra-pair association (i.e. association index), measured with joint interspecific cleaning and intraspecific behavior, is correlated with neuroendocrine mechanisms involving forebrain neuropeptides arginine vasotocin (AVT) and isotocin (IT) and b) whether these neuropeptide level shifts relate to an individual's interspecific service quality. We found that partner support (number of cleaning interactions and tactile stimulation) received by male cleaners increased with association index. When cleaners inspected clients alone, cleaners' cheating decreased with association index for females but not males. AVT levels did not differ according to sex or association level. Forebrain IT levels increased with association index for males, whereas no relationship was found for females. Finally, cleaner cheating varied between sex and forebrain IT levels. Findings indicate that variation in pairs' relationships influences male and female cleaner fish differently and contributes to the variation of brain neuropeptide levels, which is linked to distinct cooperative outcomes.